1993
DOI: 10.1113/jphysiol.1993.sp019682
|View full text |Cite
|
Sign up to set email alerts
|

Volume‐dependent K+ and Cl‐ fluxes in rat thymocytes.

Abstract: SUMMARY1. Hypotonic stress unmasked inward and outward K+ and Cl-movements in rat thymocytes. This KCl flux stimulation was reduced by DIOA (dihydroindenyl-oxyalkanoic acid), but not by DIDS (4,4'-diisothiocyanostilbene-2,2'-disulphonate), quinidine, DPAC 144 (5-nitro-2-(2-phenylethyl-amino)-benzoic acid), bumetanide or ouabain.2. In isotonic media (308 + 5 mosmol kg-'), the cells exhibited the following DIOA-(ii) a Cl-efflux of 68 + 21 mmol (I cells. h)-1 (n = 3), (iii) a Rb+ influx of 9-7 + 3 9 mmol (1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…2) (22 + 0-5 x 10-5 mol 1-l) similar to that inhibiting K+-Cl-co-transport in rat thymocytes (Soler et al 1993) and red blood cells ( RVD can be described by means of two parameters: Cmax, the maximal RVD capacity and ti, the time where RVD equals Cmax/2 (Fig. 3).…”
Section: The Effect Of Anisotonicity and Ion Substitutionmentioning
confidence: 99%
See 4 more Smart Citations
“…2) (22 + 0-5 x 10-5 mol 1-l) similar to that inhibiting K+-Cl-co-transport in rat thymocytes (Soler et al 1993) and red blood cells ( RVD can be described by means of two parameters: Cmax, the maximal RVD capacity and ti, the time where RVD equals Cmax/2 (Fig. 3).…”
Section: The Effect Of Anisotonicity and Ion Substitutionmentioning
confidence: 99%
“…We have previously found that rat thymocyte membranes have a 1: 1 K+-Cl-cotransport system (Soler, Rota, Hannaert, Cragoe & Garay, 1993). A similar cotransport system was well characterized in red blood cells, where it catalyses regulatory volume decrease (RVD; Kregenow, 1981;Lauf, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations